Electrode foil and preparation method thereof
By using organic/inorganic hybrid electrolyte gel liquid composition to form a conductive layer and forming chemical bonds with the metal oxide layer, the problem of complex preparation process of solid-state aluminum electrolytic capacitors and insufficient binding force of the conductive layer is solved, and higher high-frequency performance and stability are achieved.
Patent Information
- Application Number
- CN202411750739.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-11
AI Technical Summary
The preparation process of existing solid-state aluminum electrolytic capacitors is complicated, and the binding force and cross-linking degree of the conductive layer on the surface of the metal oxide layer in the melted foil is insufficient, resulting in poor high-frequency performance, stability and working efficiency of the capacitor.
Using an organic/inorganic hybrid electrolyte solution composition, conductive polymer, silane coupling agent-terminated polyurethane or oligomeric isocyanate, and silica sol or modified silica sol are mixed to form an adhesive conductive layer, and chemical bonds are formed with the metal oxide layer through the curing process to improve the adhesion and crosslinking of the conductive layer.
Improves the high-frequency performance and stability of the capacitor, manifested as lower loss tangent (tanδ) and equivalent series resistance (ESR), thereby improving the working efficiency of the capacitor.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of advanced functional materials, and in particular relates to an electrode foil and a preparation method thereof. Background Art
[0002] With the development of electronic technology, electrolytic capacitors, as discrete components that cannot be integrated into electronic products, are currently developing in the direction of small size, large capacity, low cost, high frequency and low impedance. Among them, aluminum electrolytic capacitors have the characteristics of excellent performance, large capacity, low price, easy processing, and convenient use. Therefore, they are widely used in electronic equipment, instruments, electromechanical, home appliances and other electronic products. Solid aluminum electrolytic capacitors have higher conductivity and high frequency performance, especially lower loss tangent and equivalent series resistance performance. At the same time, the electrode material is a solid polymer compound, there is no risk of capacitor explosion, the conductive polymer is highly stable, and the prepared capacitor has a longer life. It is the mainstream direction of electrolytic capacitor development.
[0003] However, the preparation process of solid aluminum electrolytic capacitors is complicated, especially the corrosion- and chemical-formed foil needs to be immersed in a conductive polymer and oxidant solution, and the polymerization reaction between the conductive polymer and the oxidant is difficult to control and has high uncertainty, thus affecting the performance and yield of the capacitor. To solve this problem, Chinese patents CN104409213A and CN104409212A propose to apply a conductive polymer dispersion on the metal oxide layer of the chemical foil obtained by corrosion and chemical formation of the plain foil, and form an electrode layer on the metal oxide layer by means of high-temperature curing or radiation curing, thereby preparing an electrode foil, which is then used to prepare a complete electrolytic capacitor through related processes. This method simplifies the preparation process of the capacitor and improves the performance and manufacturing yield of the capacitor.
[0004] However, the problem with this process of coating and curing the conductive polymer dispersion on the surface of the chemical foil is that the bonding strength (adhesion) of the conductive layer to the metal oxide layer on the surface of the chemical foil and the degree of cross-linking within the conductive layer need to be improved, the porosity of the conductive layer itself needs to be further reduced, and the degree of cross-linking of the conductive layer needs to be increased to form a denser coating on the surface of the metal oxide layer, thereby improving the high-frequency performance, stability and working efficiency of the solid aluminum electrolytic capacitor, thereby meeting the increasingly stringent demands in the field of electrolytic capacitors. Summary of the invention
[0005] In view of the defects of the prior art, the technical problem to be solved by the present invention is to provide an organic / inorganic hybrid electrolyte gel composition, which is coated on a chemical foil and cured to form a conductive layer and further prepared into an electrode foil. The capacitor prepared by the electrode foil has better high-frequency performance and stability, which is reflected in the capacitor having a lower loss tangent (tanδ) and equivalent series resistance (ESR).
[0006] In a first aspect, an electrolyte gel composition comprises a conductive polymer, a polyurethane or oligomeric isocyanate terminated with a silane coupling agent, and a silica sol or a silica sol modified with a silane coupling agent;
[0007] Wherein, the conductive polymer is a composition comprising a π-conjugated conductive polymer and a polyanion, the polyurethane or oligomeric isocyanate terminated by a silane coupling agent uses a polyurethane or oligomeric isocyanate terminated by a silane coupling agent containing an amino group or an imino group, and the silica sol modified by a silane coupling agent uses a silica sol modified by a silane coupling agent containing an epoxy group;
[0008] Preferably, the π-conjugated conductive polymer is selected from polythiophene or polythiophene derivatives, including: polythiophene, poly (3-methylthiophene), poly (3-ethylthiophene), poly (3-propylthiophene), poly (3-butylthiophene), poly (3-hexylthiophene), poly (3-heptylthiophene), poly (3-octylthiophene), poly (3-decylthiophene), poly (3-dodecylthiophene), poly (3-octadecylthiophene), poly (3-bromothiophene), poly ( 3-chlorothiophene), poly(3-iodothiophene), poly(3-cyanothiophene), poly(3-phenylthiophene), poly(3,4-dimethylthiophene), poly(3,4-dibutylthiophene), poly(3-hydroxythiophene), poly(3-methoxythiophene), poly(3-ethoxythiophene), poly(3-butoxythiophene), poly(3-hexyloxythiophene), poly(3-heptyloxythiophene), poly(3-octyloxythiophene), poly(3-decyloxythiophene), poly(3-methoxythiophene), poly(3-ethoxythiophene), poly(3-butoxythiophene), poly(3-hexyloxythiophene), poly(3-heptyloxythiophene), poly(3-octyloxythiophene), poly(3-decyloxythiophene), poly(3-hydroxy ...hydroxythiophene), poly(3-hydroxythiophene), poly(3- (3-dodecyloxythiophene), poly (3-octadecyloxythiophene), poly (3,4-dihydroxythiophene), poly (3,4-dimethoxythiophene), poly (3,4-diethoxythiophene), poly (3,4-dipropoxythiophene), poly (3,4-dibutoxythiophene), poly (3,4-dihexyloxythiophene), poly (3,4-diheptyloxythiophene), poly (3,4-dioctyloxythiophene), poly (3,4-didecyloxythiophene), Poly(3,4-didodecyloxythiophene), poly(3,4-ethylenedioxythiophene), poly(3,4-propylenedioxythiophene), poly(3,4-butylenedioxythiophene), poly(3-methyl-4-methoxythiophene), poly(3-methyl-4-ethoxythiophene), poly(3-carboxythiophene), poly(3-methyl-4-carboxythiophene), poly(3-methyl-4-carboxyethylthiophene), poly(3-methyl-4-carboxybutylthiophene);
[0009] More preferably, the π-conjugated conductive polymer is selected from poly(3,4-ethylenedioxythiophene);
[0010] Preferably, the polyanion is selected from polystyrene sulfonic acid, polyvinyl sulfonic acid, polyallyl sulfonic acid and their corresponding metal salts;
[0011] More preferably, the polyanion is selected from polystyrene sulfonate;
[0012] Preferably, the silane coupling agent-terminated polyurethane or silane coupling agent-terminated oligomeric isocyanate uses 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane or bis(3-trimethoxysilylpropyl)amine-terminated polyurethane or oligomeric isocyanate;
[0013] Preferably, the process of silane coupling agent blocking polyurethane or oligomeric isocyanate is that the amino group or imino group of the silane coupling agent reacts with the isocyanate group on the polyurethane or oligomeric isocyanate;
[0014] Preferably, the polyurethane is polyester polyurethane or polyether polyurethane;
[0015] Preferably, the oligomeric isocyanate is an aliphatic isocyanate trimer, and more preferably, the oligomeric isocyanate comprises: any one or a combination of two of a hexamethylene diisocyanate (HDI) trimer and an isophorone diisocyanate (IPDI) trimer;
[0016] Preferably, the silica sol is colloidal silicon dioxide dispersed in water or an organic solvent;
[0017] Preferably, the silane coupling agent-modified silica sol uses γ-glycidyloxypropyltrimethoxysilane or γ-glycidyloxypropyltriethoxysilane-modified silica sol.
[0018] Preferably, the method of modifying the silica sol with a silane coupling agent is to carry out an ester exchange reaction between the silane coupling agent and ethyl orthosilicate in water and / or an alcohol solvent;
[0019] Preferably, the alcohol solvent includes any one of methanol, ethanol, n-propanol or isopropanol, and more preferably, the alcohol solvent is isopropanol;
[0020] Preferably, the transesterification reaction uses tetrabutyl titanate as a transesterification catalyst;
[0021] Preferably, the amount of the conductive polymer in the electrolyte gel composition is 15 to 35 wt %, and more preferably, the amount of the conductive polymer is 20 to 30 wt %;
[0022] Preferably, the amount of the silane coupling agent-terminated polyurethane or the silane coupling agent-terminated oligomeric isocyanate in the electrolyte gel composition is 45-65wt%, and more preferably, the amount of the silane coupling agent-terminated polyurethane or the silane coupling agent-terminated oligomeric isocyanate is 45-60wt%;
[0023] Preferably, the amount of the silane coupling agent modified silica sol in the electrolyte gel composition is 10-20 wt %, and more preferably, the amount of the silane coupling agent modified silica sol is 10-15 wt %.
[0024] Furthermore, the electrolyte gel composition also includes a wax emulsion, which is a multiphase system emulsion in which natural wax, synthetic wax and other materials are dispersed in water under the action of an emulsifier, wherein the wax emulsion is selected from: a natural wax emulsion or a synthetic wax emulsion;
[0025] Preferably, the amount of the wax emulsion is 1 to 15 wt %, and more preferably, the amount of the wax emulsion is 1 to 10 wt %;
[0026] Furthermore, the electrolyte gel composition further comprises a high conductivity aid, which is selected from at least one compound or a combination of multiple compounds selected from compounds having at least two hydroxyl groups, compounds having at least one hydroxyl group and at least one carboxyl group, compounds having an amide group, compounds having an imide group, and compounds having a glycidyl group;
[0027] Preferably, the high conductivity aid is selected from compounds having at least 2 hydroxyl groups;
[0028] More preferably, the high conductivity aid is selected from any one of ethylene glycol and propylene glycol or a combination of the two;
[0029] Preferably, the amount of the high conductivity auxiliary agent is 5 to 15 wt %.
[0030] Furthermore, the electrolyte glue composition also includes a leveling agent and a defoaming agent, the leveling agent is selected from: any one of a polyether leveling agent, a polysiloxane leveling agent or a polyether modified polysiloxane leveling agent, and the defoaming agent is selected from: any one of a silicone defoaming agent, a polyether defoaming agent or a silicone polyether defoaming agent.
[0031] Preferably, the amount of the leveling agent is 0.1 to 1.0 wt%, and the amount of the defoaming agent is 0.1 to 1.0 wt%;
[0032] In a second aspect, the method for preparing the above-mentioned electrolyte gel composition comprises mixing all components and stirring them evenly.
[0033] In a third aspect, a conductive layer is obtained by curing the above-mentioned electrolyte gel composition at 100-200°C.
[0034] In a fourth aspect, an electrode foil comprises: a metal substrate, a metal oxide layer and the conductive layer described above;
[0035] The material of the metal substrate includes: aluminum, titanium, tantalum, niobium and corresponding alloys. Preferably, the material of the metal substrate includes: aluminum or an alloy formed by aluminum and copper, magnesium, silicon and zinc.
[0036] The metal oxide layer is an oxide layer formed on the surface of the metal substrate.
[0037] In a fifth aspect, the method for preparing the electrode foil described above comprises: coating the electrolyte gel composition described above onto the metal oxide layer of the metal substrate.
[0038] Preferably, the coating thickness is 50 to 150 μm, and more preferably, the coating thickness is 125 μm.
[0039] Preferably, the preparation method further comprises: curing the conductive layer on the metal oxide layer at 100-200° C. after coating.
[0040] In a sixth aspect, a capacitor is prepared using the electrode foil described above.
[0041] The beneficial effects of the above technical solution are:
[0042] The present application uses silane coupling agent-terminated polyurethane or isocyanate and silica sol or silane coupling agent-modified silica sol as adhesive components to effectively hybridize organic resin and inorganic silica sol, and on this basis, adds a conductive electrolyte glue to form an adhesive conductive layer. This inorganic / organic hybrid conductive layer condenses with the -OH of the metal oxide layer during the curing process to form Si-OM, thereby achieving chemical bonding between the conductive layer and the metal oxide layer, thereby achieving permanent bonding, thereby improving the adhesion of the conductive layer to the porous metal oxide layer. The organic resin terminated with the silane coupling agent and the inorganic silica sol can also form Si-O-Si bonds through condensation reaction, thereby improving the crosslinking degree and density of the conductive layer and making the internal porosity of the conductive layer lower. At the same time, the silane coupling agent is used for resin termination, and the contact points between Si-OM and the metal oxide layer are more and more tightly combined, so that the contact resistance between the conductive layer and the formed foil becomes smaller, and the heat generation is reduced. When the capacitor is in use, the temperature rise rate becomes slower. The electrode foil prepared in this way has better high-frequency performance and stability when used in capacitors, which is reflected in the prepared capacitors having lower loss tangent (tanδ) and equivalent series resistance (ESR). DETAILED DESCRIPTION
[0043] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0044] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0045] If the specific experimental conditions are not specified in the examples, they are usually based on the conventional conditions in the field or the conditions recommended by the reagent company; the materials, reagents, etc. used in the examples can be purchased through commercial channels unless otherwise specified.
[0046] Preparation of silane coupling agent modified silica sol: 52 g (0.25 mol) of tetraethyl orthosilicate and 236.3 g (1.0 mol) of silane coupling agent KH560 (3-glycidyloxypropyltrimethoxysilane) were added into a three-necked flask, stirring was started, and then 72 g of water and 30 g of isopropanol were added as solvents under stirring. After heating to 82° C., 1.5 g of tetrabutyl titanate, an ester exchange catalyst, was added and stirred sufficiently. The reaction temperature was maintained at 82° C. and stirred for 4 hours to obtain silane coupling agent modified silica sol.
[0047] Preparation of silane coupling agent-terminated polyurethane: 100 g (0.1 mol) of polyethylene glycol 1000 (PEG1000, Jiangsu Hai'an Petrochemical Plant) with a molecular weight of 1000 and 289 g (1.3 mol) of isophorone diisocyanate (IPDI, Yantai Wanhua) were added to a three-necked flask, stirring was started, 0.8 g of catalyst dibutyltin dilaurate (DBTDL) was added under stirring, the temperature was raised to 85° C. and reacted for 2 hours, then 109.3 g (0.32 mol) of KH170 (bis(3-trimethoxysilylpropyl)amine, Hangzhou Jessica Chemical) was added, the temperature was maintained at 85° C. and the reaction was continued for 2 hours, and finally the temperature was lowered to 50° C., unreacted monomers were removed by reduced pressure distillation, and then the reaction was terminated to obtain a silane coupling agent-terminated waterborne polyurethane.
[0048] 380 g of the above waterborne polyurethane was weighed and dispersed in 280 g of a water / isopropanol mixed solution (wherein the mass ratio of water to isopropanol was 3:1) for later use.
[0049] Preparation of silane coupling agent-terminated isocyanate oligomers: First, nitrogen was introduced into the reaction bottle to remove water vapor and oxygen therein, 101 g (0.2 mol) of HDI trimer (Desmodur N3300 from Covestro) was added into a three-necked flask, stirring was started, 213.5 g (0.625 mol) of KH170 (bis(3-trimethoxysilylpropyl)amine) and 1.0 g of catalyst dibutyltin dilaurate (DBTDL) were added under stirring, and nitrogen was continuously introduced for protection. The temperature was raised to 70°C and reacted for 2 hours, then cooled to room temperature, and added to 200 g of a water / isopropanol mixed solution (wherein the mass ratio of water to isopropanol was 3:1) for later use.
[0050] Example 1
[0051] The electrolyte gel solution is prepared by weighing 100g of the above-mentioned aqueous polyurethane dispersion, 54g of conductive polymer, 10g of wax emulsion, 25g of silane coupling agent modified silica sol, 15g of ethylene glycol, 1g of leveling agent, and 1g of defoaming agent, mixing and stirring evenly, and then coating it on the surface of the metal oxide layer of the chemical foil, with a coating thickness of 125μm, and then baking it at 140°C for 20min, thereby obtaining an electrode foil. Subsequently, the electrode foil coated with the electrolyte gel solution is assembled into an aluminum electrolytic capacitor in accordance with the procedures of opening the foil, riveting, winding, impregnation, and sealing. At a working voltage of 25V, the electrostatic capacitance, capacitor loss tangent, and equivalent series resistance of the capacitor are tested, and the test method is consistent with the test method of conventional solid electrolytic capacitors.
[0052] Among them, the higher the electrostatic capacitance of the capacitor, the stronger the ability of the capacitor to store charge. Under the same voltage, a capacitor with a high capacitance value can store more charge; the higher the loss tangent value of the capacitor, the more energy the capacitor converts into heat energy during operation instead of being stored in the electric field, which causes the capacitor to heat up and reduces its efficiency; the higher the equivalent series resistance of the capacitor, the more heat the capacitor generates during operation and the greater the energy loss, that is, the capacitor consumes more energy during the charging and discharging process and its efficiency decreases. It can be seen that the higher the electrostatic capacitance of the capacitor, the better the performance, and the lower the loss tangent value and equivalent series resistance of the capacitor, the more conducive to improving the working efficiency of the capacitor.
[0053] Example 2
[0054] The electrolyte gel solution was prepared by weighing 105 g of the above aqueous polyurethane dispersion, 50 g of conductive polymer, 10 g of wax emulsion, 26 g of silane coupling agent modified silica sol, 14 g of ethylene glycol, 1 g of leveling agent, and 1 g of defoaming agent, mixing and stirring evenly, coating the mixture on the metal oxide layer surface of the chemical foil, with a coating thickness of 125 μm, and then baking the mixture at 150° C. for 20 min, thereby obtaining an electrode foil. The rest of the test parts were the same as those in Example 1.
[0055] Example 3
[0056] The electrolyte gel solution was prepared by weighing 110 g of the aqueous polyurethane dispersion, 48 g of the conductive polymer, 8 g of the wax emulsion, 28 g of the silane coupling agent-modified silica sol, 18 g of ethylene glycol, 1 g of the leveling agent, and 1 g of the defoaming agent, mixing and stirring them evenly, and then coating them on the surface of the metal oxide layer of the chemical foil with a coating thickness of 125 μm, and then baking them at 110° C. for 30 min, thereby obtaining an electrode foil. The rest of the test parts were the same as those in Example 1.
[0057] Example 4
[0058] The electrolyte gel solution was prepared by weighing 100 g of the aqueous polyurethane dispersion, 56 g of the conductive polymer, 14 g of the wax emulsion, 24 g of the silane coupling agent-modified silica sol, 16 g of propylene glycol, 1 g of the leveling agent, and 1 g of the defoaming agent, mixing and stirring the mixture evenly and coating the mixture on the surface of the metal oxide layer of the chemically formed foil with a coating thickness of 125 μm, and then baking the mixture at 160° C. for 20 min to obtain an electrode foil. The rest of the test parts were the same as those in Example 1.
[0059] Example 5
[0060] The electrolyte gel solution was prepared by weighing 110 g of the above aqueous polyurethane dispersion, 50 g of conductive polymer, 12 g of wax emulsion, 30 g of silane coupling agent modified silica sol, 15 g of propylene glycol, 1 g of leveling agent, and 1 g of defoaming agent, mixing and stirring evenly, coating the mixture on the metal oxide layer surface of the chemically formed foil, with a coating thickness of 125 μm, and then baking the mixture at 180° C. for 15 min, thereby obtaining an electrode foil. The rest of the test parts were the same as those in Example 1.
[0061] Example 6
[0062] The electrolyte gel solution was prepared by weighing 130 g of silane coupling agent blocked isocyanate oligomer, 60 g of conductive polymer, 12 g of wax emulsion, 36 g of silane coupling agent modified silica sol, 18 g of propylene glycol, 1 g of leveling agent, and 1 g of defoamer, mixing and stirring them evenly, coating them on the surface of the metal oxide layer of the chemical foil, with a coating thickness of 125 μm, and then baking them at 150° C. for 30 min, thereby obtaining an electrode foil. The rest of the test parts were the same as those in Example 1.
[0063] Example 7
[0064] The electrolyte gel solution was prepared by weighing 120 g of silane coupling agent blocked isocyanate oligomer, 56 g of conductive polymer, 12 g of wax emulsion, 32 g of silane coupling agent modified silica sol, 15 g of ethylene glycol, 1 g of leveling agent, and 1 g of defoamer, mixing and stirring them evenly, coating them on the surface of the metal oxide layer of the chemical foil, with a coating thickness of 125 μm, and then baking them at 170° C. for 20 min, thereby obtaining an electrode foil. The rest of the test parts were the same as those in Example 1.
[0065] Example 8
[0066] The electrolyte gel solution was prepared by weighing 120 g of silane coupling agent blocked isocyanate oligomer, 54 g of conductive polymer, 12 g of wax emulsion, 33 g of Nissan Chemical's MEK-AC-2202 silica sol, 16 g of ethylene glycol, 1 g of leveling agent, and 1 g of defoamer, mixing and stirring evenly, coating the mixture on the metal oxide layer surface of the chemical foil, with a coating thickness of 125 μm, and then baking at 170° C. for 20 min to obtain an electrode foil. The rest of the test parts were the same as those in Example 1.
[0067] Example 9
[0068] The electrolyte gel solution was prepared by weighing 110 g of the above aqueous polyurethane dispersion, 50 g of conductive polymer, 12 g of wax emulsion, 28 g of Nissan Chemical's MEK-AC-2202 silica sol, 15 g of ethylene glycol, 1 g of leveling agent, and 1 g of defoamer, mixing and stirring them evenly, and then coating them on the surface of the metal oxide layer of the chemical foil with a coating thickness of 125 μm, and then baking them at 160° C. for 30 min to obtain an electrode foil. The rest of the test parts were the same as in Example 1.
[0069] Comparative Example 1
[0070] Preparation of electrolyte glue, weigh aliphatic polyether waterborne polyurethane LANXESS 100 g of 737 (pre-dispersed in a mixed solution of water / isopropanol with a mass ratio of 3:1), 5 g of silane coupling agent KH540 (3-aminopropyltrimethoxysilane), 8 g of silane coupling agent KH560, 54 g of conductive polymer, 10 g of wax emulsion, 16 g of ethylene glycol, 1 g of leveling agent, and 1 g of defoaming agent were mixed and stirred evenly and then coated on the surface of the metal oxide layer of the chemical foil with a coating thickness of 125 μm, and then baked at 140° C. for 20 min to obtain an electrode foil. The remaining test parts were the same as those in Example 1.
[0071] Comparative Example 2
[0072] Preparation of electrolyte glue, weigh aliphatic polyether waterborne polyurethane LANXESS 447-05 (pre-dispersed in a mixed solution of water / isopropanol with a mass ratio of 3:1) 105g, silane coupling agent KH170 6g, silane coupling agent KH560 8g, conductive polymer 50g, Nissan Chemical America Corporation MEK-AC-2202 silica sol 25g, wax emulsion 12g, ethylene glycol 15g, leveling agent 1g, defoaming agent 1g, mix and stir evenly, and then apply it on the surface of the metal oxide layer of the chemical foil, the coating thickness is 125μm, and then bake at 180°C for 15min, thereby obtaining an electrode foil. The rest of the test parts are the same as Example 1.
[0073] Comparative Example 3
[0074] The electrolyte gel solution was prepared by weighing 120 g of silane coupling agent blocked isocyanate oligomer, 56 g of conductive polymer, 12 g of wax emulsion, 8 g of silane coupling agent KH560, 15 g of ethylene glycol, 1 g of leveling agent, and 1 g of defoamer, mixing and stirring them evenly, and then coating them on the surface of the metal oxide layer of the chemical foil with a coating thickness of 125 μm, and then baking them at 170° C. for 20 min to obtain an electrode foil. The rest of the test parts were the same as those in Example 1.
[0075] Comparative Example 4
[0076] The electrolyte gel solution was prepared by weighing 100 g of Asahi Kasei WM44-L70G water-based blocked isocyanate, 55 g of conductive polymer, 13 g of wax emulsion, 28 g of silane coupling agent modified silica sol, 6 g of silane coupling agent KH550 (3-aminopropyltriethoxysilane), 16 g of propylene glycol, 1 g of leveling agent, and 1 g of defoaming agent, mixing and stirring evenly, and then coating the mixture on the metal oxide layer surface of the formed foil with a coating thickness of 125 μm, and then baking the mixture at 170° C. for 20 min to obtain an electrode foil. The rest of the test parts were the same as those in Example 1.
[0077] In the above embodiments and comparative examples, the conductive polymer is selected from poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate (abbreviated as: PEDOT:PSS), the wax emulsion is selected from synthetic wax emulsion A-535 (Dongguan Xinghong Chemical Materials Co., Ltd.), the leveling agent is selected from N3248 polyether modified polysiloxane wetting and leveling agent (Guangzhou Hongxin Chemical Additive Co., Ltd.), and the defoaming agent is selected from TEGO Airex 901W silicone polyether defoaming agent (Evonik, Germany).
[0078] The comparison results of the electrostatic capacitance, capacitor loss tangent and equivalent series resistance performance of the electrode foil prepared in Examples 1-9 and Comparative Examples 1-4 are shown in Table 1. The working voltage in the test was fixed at 25V.
[0079] Table 1
[0080] sample Capacitance(μF) Loss tangent (tanδ) Equivalent series resistance (mΩ) Example 1 74.3 0.156 20.1 Example 2 77.6 0.182 19.8 Example 3 75.8 0.171 21.2 Example 4 76.0 0.160 20.8 Example 5 75.4 0.189 20.3 Example 6 80.3 0.180 18.7 Example 7 77.9 0.179 19.5 Example 8 74.4 0.173 21.6 Example 9 73.8 0.188 22.0 Comparative Example 1 65.5 0.350 45.7 Comparative Example 2 74.2 0.282 36.4 Comparative Example 3 68.3 0.329 40.8 Comparative Example 4 72.7 0.304 37.6
[0081] It can be seen from Table 1 that under the same test conditions, the electrostatic capacitance of Examples 1-9 is higher, and the loss tangent value and the equivalent series resistance are lower. This is because the structure formed after the electrolyte gel of Examples 1-9 is coated on the surface of the formed foil is more compact, and the Si-OR in the polyurethane or isocyanate blocked by the silane coupling agent is hydrolyzed into Si-OH in water and then undergoes ester exchange or condensation reaction with the Si-OR of other silane coupling agents or the Si-OH in the modified silica sol to produce Si-O-Si bonds with better high temperature resistance and aging resistance, forming a denser surface conductive coating, and the silica sol is modified by epoxy-containing KH560 to introduce epoxy groups into the coating system, and its own Si-OH can react with the metal oxide layer to form a Si-OM chemical bond, thereby improving the adhesion of the conductive layer to the metal substrate, thereby improving the performance of the capacitor, especially reducing the energy loss generated at high frequency. Compared with Comparative Examples 1-4, the loss tangent and equivalent series resistance of Examples 1-9 are significantly lower, thereby avoiding the capacitor from increasing heat and causing a decrease in efficiency, and improving the high-frequency performance and working efficiency of the capacitor.
[0082] In addition, it can be seen from Table 1 that Comparative Example 1 does not use modified silica sol, and the amino-containing silane coupling agent KH540 is not terminated by reaction with the polyurethane resin. Therefore, the adhesion effect between the conductive layer and the metal oxide layer is relatively poor, and the Si-O-Si bond is only formed by condensation between the silane coupling agent Si-OR. The cross-linking density inside the conductive layer is not high, resulting in lower electrostatic capacitance, higher loss tangent and equivalent series resistance, and lower energy stored in the capacitor, that is, more energy will be consumed in the charging and discharging process of the capacitor.
[0083] Comparative Example 2 adds silica sol on the basis of Comparative Example 1, but the aminosilane-containing silane coupling agent KH170 does not end-cap the polyurethane resin, and the epoxy-containing silane coupling agent KH560 is also not modified with the silica sol, resulting in differences in chemical structure, polarity, and surface energy between the silica sol and the polyurethane resin, resulting in a higher mixing free energy between the two, which makes them tend to separate rather than mix thermodynamically, and is not conducive to the adhesion of the conductive layer and the metal oxide layer. Although the electrostatic capacitance is increased, the loss tangent and the equivalent series resistance are still too high, resulting in poor capacitor performance.
[0084] Comparative Example 3 uses KH170-terminated isocyanate oligomers but does not add silica sol, resulting in a lack of Si-O-Si bonds in the hybrid conductive layer, low adhesion between the conductive layer and the metal oxide layer, and no significant reduction in the loss tangent and equivalent series resistance of the capacitor finally prepared.
[0085] Comparative Example 4 uses epoxy-containing silane coupling agent KH560 to modify silica sol, and amino-containing silane coupling agent KH170, but no coupling agent is used to cap the isocyanate, resulting in poor compatibility between the silicon component and the organic resin. Although the electrostatic capacitance is similar to that of Examples 1-9, the capacitor loss tangent and equivalent series resistance are still high.
[0086] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to perform equivalent replacements on parts thereof. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention. Although the above describes the specific implementation methods of the present invention, it is not intended to limit the protection scope of the present invention. Those skilled in the art should understand that, based on the technical solution of the present invention, various modifications or deformations that can be made by those skilled in the art without creative labor are still within the protection scope of the present invention.
Claims
1. An electrolyte gel composition, characterized in that: It includes conductive polymer, polyurethane or oligomeric isocyanate terminated with silane coupling agent, and silica sol or silica sol modified with silane coupling agent; Wherein, the conductive polymer is a composition comprising a π-conjugated conductive polymer and a polyanion, the polyurethane or oligomeric isocyanate terminated by a silane coupling agent uses a polyurethane or oligomeric isocyanate terminated by a silane coupling agent containing an amino group or an imino group, and the silica sol modified by a silane coupling agent uses a silica sol modified by a silane coupling agent containing an epoxy group; The process of silane coupling agent blocking polyurethane or oligomeric isocyanate is that the amino group or imino group of the silane coupling agent reacts with the isocyanate group on the polyurethane or oligomeric isocyanate; Wherein, silica sol is colloidal silicon dioxide dispersed in water or an organic solvent; The method for modifying the silica sol with a silane coupling agent is to carry out an ester exchange reaction between the silane coupling agent and ethyl orthosilicate in water and / or an alcohol solvent; Preferably, the polyurethane is polyester polyurethane or polyether polyurethane; Preferably, the oligomeric isocyanate is an aliphatic isocyanate trimer; Preferably, the alcohol solvent includes any one of methanol, ethanol, n-propanol or isopropanol.
2. The electrolyte gel composition according to claim 1, wherein the amount of the conductive polymer in the electrolyte gel composition is 15 to 35 wt%; Preferably, the amount of the silane coupling agent-terminated polyurethane or silane coupling agent-terminated oligomeric isocyanate in the electrolyte gel composition is 45 to 65 wt %; Preferably, the amount of the silane coupling agent modified silica sol in the electrolyte gel composition is 10-20 wt%.
3. The electrolyte gel composition according to claim 1, characterized in that: The electrolyte gel composition also includes a wax emulsion, which is a multiphase system emulsion in which natural wax, synthetic wax and other materials are dispersed in water under the action of an emulsifier, wherein the wax emulsion is selected from: a natural wax emulsion or a synthetic wax emulsion; Preferably, the amount of wax emulsion used is 1 to 15 wt%.
4. The electrolyte gel composition according to claim 1, characterized in that: The electrolyte gel composition further includes a high conductivity aid, which is selected from at least one compound or a combination of multiple compounds selected from compounds having at least two hydroxyl groups, compounds having at least one hydroxyl group and at least one carboxyl group, compounds having an amide group, compounds having an imide group, and compounds having a glycidyl group; Preferably, the high conductivity aid is selected from compounds having at least 2 hydroxyl groups; Preferably, the amount of the high conductivity auxiliary agent is 5 to 15 wt %.
5. The electrolyte gel composition according to claim 1, characterized in that: The electrolyte glue composition also includes a leveling agent and a defoaming agent, the leveling agent is selected from: any one of a polyether leveling agent, a polysiloxane leveling agent or a polyether-modified polysiloxane leveling agent, and the defoaming agent is selected from: any one of an organic silicon defoaming agent, a polyether defoaming agent or an organic silicon polyether defoaming agent; Preferably, the amount of the leveling agent is 0.1-1.0 wt %, and the amount of the defoaming agent is 0.1-1.0 wt %.
6. The method for preparing the electrolyte gel composition according to any one of claims 1 to 5, characterized in that: This involves mixing all ingredients together and stirring until smooth.
7. A conductive layer obtained by curing the electrolyte gel composition according to any one of claims 1 to 5 at 100-200°C.
8. An electrode foil comprising: A metal substrate, a metal oxide layer and the conductive layer according to claim 7; Wherein, the material of the metal substrate includes: aluminum, titanium, tantalum, niobium and corresponding alloys; Preferably, the material of the metal substrate includes: aluminum or an alloy formed by aluminum and copper, magnesium, silicon, or zinc; The metal oxide layer is an oxide layer formed on the surface of the metal substrate.
9. The method for preparing the electrode foil according to claim 8, comprising: Applying the electrolyte gel composition according to any one of claims 1 to 5 onto the metal oxide layer of the metal substrate; Preferably, the coating thickness is 50 to 150 μm.
10. A capacitor made from the electrode foil according to claim 8.
Citation Information
Patent Citations
Formed foil post-processing method, electrode foil and capacitor
CN104409212A
Electrolyte glue solution for post-treatment of formed foil, electrode foil and capacitor
CN104409213A
Cited By
Conductive coating composition and preparation method thereof, laminated body and liquid crystal display
CN120829712A